Analisis Pengaruh Harga Beras, Cadangan Devisa, Dan Rata-Rata Konsumsi Beras per Kapita Seminggu Terhadap Impor Beras Di Indonesia Tahun 2008- 2017 - Niken Puspitasari; Lucia Rita Indrawati; Sudati Nur Sarfiah (Universitas Tidar, 2019)
Food is a basic human need for life, so food commodities are the top priority in the consumptionof the Indonesian population Rice is the most excessively consumed food commodity by theIndonesian population. Maintaining the availability of domestic rice by importing rice as a government effort to maintain price stability, domestic rice supply and rice reserves when natural disasters occur. When itis still consumed by the majority of the Indonesian population, the availability is very crucial. The constraints faced by the supply of rice commodities are production problems and price stability. Domestic production still does not fulfill consumption so rice imports must be made. The purpose of this research is to determine the effect of rice imports as a government policy to realize food security and food self-sufficiency in Indonesia by knowing the simultaneous and partial influence of rice prices, foreign exchange reserves and rice consumption on rice imports in Indonesia in 2008-2017, and to analyze the most dominant variable affecting rice imports in Indonesia for the period 2008-2017. The data analysis technique used is regression analysis and classic assumption test. The results how simultaneously the variable price of rice, foreign exchange reserves and rice consumption have a significant effect on rice imports in Indonesia in 2008-2017. Partially the rice price variable and rice consumption have no effect on rice imports in Indonesia in 2008-2017. The variable of foreign exchange reserves has a positive and significant effect on rice imports in Indonesia in 2008-2017. Keywords: Rice Prices, Foreign Exchange Reserves, Rice Consumption, rice imports.